The Effect Of Wound Care With Palm Sugar On Diabetic Ulcer Repairing In Type 2 Diabetes Patients - Devi Ratnasari; Eva Daniati; Eti Suliyawati; Zahara Farhan (Green Publisher Indonesia, 2021)
Diabetic ulcers are one of the most common complications of type 2 diabetes mellitus. Diabetic ulcers are infected sores that develop in the lower extremities. Proper diabetic foot wound care methods will improve wound healing. One of the efforts to treat the complement to prevent infection is wound care with palm sugar. Palm sugar contains antibiotic-like substances such as vitamin C, riboflavin, vitamin A, and ascorbic acid. Dr. Slamet Garut's study aims to determine the effectiveness of wound care with palm sugar media against the repair of diabetic ulcers in patients with type 2 diabetes mellitus after hospitalization in 2021. The study used a quasi experimental research design with one group pretest and posttest design (Pre-action) and one group of subjects receiving palm sugar therapy on diabetic ulcer wounds (Post-action). The researcher used consecutive sampling techniques, samples that met the inclusion criteria could have 8 people. The wounds were treated with palm sugar for two weeks. The findings revealed that wound care with palm sugar had an effect on the repair of diabetic ulcers in patients with type 2 diabetes mellitus, with a Pvalue = 0.000. Then it is possible to conclude that treating wounds with palm sugar affects the improvement of diabetic ulcers.